Tawhidic Based Economic System: A Preliminary Conception - Hilmiyah, Nurul Hilmiyah; Possumah, Bayu Taufiq; Shaifai, Muhammad Hakimi Mohd (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2017)
This study investigates contemporary mainstream economic system, does Islamic Economics taking advantage of the shortfall of the system outlined above based on Tawhidical approach? By using descriptive qualitative method this paper proposed the appropriate of Islamic economics theorize that the Islamic system provide the ideal form of a socio-economic order. This paper found that Tawhidic based economics approaches can be focused towards seeing wholes of economics, rather than parts; seeing economics activities as a worship, rather than competition; cultivating the solidarity (charity), rather than individualism and creating the justice, rather than injustice. Thus this paper designed to provide the concept of Islamic economic system with Tawhid as the basis, to fit the philosophy of economic science and reality of human life. The paper also shows the position of Tawhid in the system and theory of economy in creating prosperity and benefit for all mankind comparing to mainstream economic system and their theory.DOI: 10.15408/aiq.v9i1.3481